Internet connectivity disruption in India (India) - Voidly (2026)
CRITICAL severity mixed detected in India. Confidence: 67%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: IN-2026-0161
Keywords: censorship; IN; mixed; critical